Os impactos da agroenergia no mercado de terras: dinâmica de preço e elasticidade de uso - Barros, Fábio Renato Turquino de (2010)
This paper aims to build a theoretical framework to support the understanding how Agroenergy may impact the farmland market in Brazil. Afterwards, analyze the impacts of Agroenergy in the land use elasticity after the introduction of flex-fuel vehicles in Brazil. Aspects related to land market, their definitions and usage characteristics, have been studied for many thinkers and economists since the late nineteenth century. Motivated by this statement, a review of related literature was done to understand the different lines of economic thought regarding the main variables related to price formation and farmland market dynamics. The neoclassical theory defends the value of farmland is inextricably linked to its production capacity. Allied to this characteristic, it is also important to understand the attributes of the land as real asset investment – related to the expectation of capital gains or capital protection. In order to contribute to this discussion, was proposed an information flowchart to identify how the variables should be correlated and impact the pricing of agricultural land. It can be argued that in the short term, the impact the Agroenergy in farmland prices is through commodity prices, features real asset, especially in the bid for capital gains and the rise of government policies related to the production of biofuels. Regarding the land use elasticity coefficient of sugar cane in Sao Paulo with respect to the expected price of ATR per ton equivalent—for sugar and ethanol—it was observed that the acreage of sugarcane has become more sensitive to variations in the price of ATR, expanding the area with less variation in the price range after the introduction of flex-fuel vehicles in the domestic market.